ERP Adoption in Higher Education: A TAM-Based Analysis of Botswana’s Technical University - Otlhomile, Boitshoko Effort; Rafifing, Neo; Mphale, Ofaletse; Mosinki, Joyce; Mabina, Alton (Journal of Information System and Informatics, 2025)
This study investigates ERP adoption at a technical university in Botswana using the Technology Acceptance Model (TAM). It examines how Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioural Intention (BI) influence Actual System Use (AU). Data were collected from administrative staff using a structured survey and analyzed using regression analysis. The results show that PEOU significantly influences both BI (R² = 0.964, p = 0.0029) and PU (R² = 0.864, p = 0.022), indicating that system usability is crucial for ERP adoption. Furthermore, PEOU positively impacts PU (R² = 0.817, p = 0.035), and BI strongly predicts AU (R² = 0.821, p = 0.034). These findings highlight the importance of user-friendly interfaces, comprehensive training programs, and institutional support to ensure successful ERP implementation. The research provides valuable insights for universities aiming to enhance operational efficiency, streamline data management, and improve decision-making processes through effective ERP adoption, particularly in developing countries like Botswana.